Investigating the Relationship between Creative Thinking and Entrepreneurial Spirit with STEMC-Based Project-Based Learning Models - Zatya, I.; Sulastri, S.; Saminan, S.; Rahmi, M. (Universitas Negeri Yogyakarta, 2024)
Creative thinking is the cornerstone of entrepreneurship to encourage innovative ideas and entrepreneurial opportunities. The research aimed to determine a significant correlation between creative thinking and entrepreneurial spirit. The study used a correlation design. The sample was selected using purposive sampling. The sample was students in class X of SMAN 3 Langsa City. Data collection used a description test to determine the student's level of creative thinking and questionnaires to determine the student's entrepreneurial spirit. The data were tested using parametric statistics in the form of Pearson Product Moment correlations, which were analyzed using SPSS 20 statistical techniques. The results obtained that the correlation coefficient was 0.518. It shows that there is a correlation with sufficient criteria with an interpretation score between 0.40 <r â‰¤ 0.60. Furthermore, with df = 52, it obtained a significance level of 0.05 at 0.2732, so rxy = 0.518 > t table 0.2732. Then, Ha is accepted and Ho is rejected, which indicates a significant correlation between creative thinking and students' entrepreneurial spirit. It is recommended that in the future, educators implement entrepreneurship-based STEM learning, which focuses on creativity and fosters students' confidence to start entrepreneurship.